Marital Satisfaction and Life Satisfaction: The Mediating Effect of Spirituality - Figen Kasapoğlu; Ayşenur Yabanigül (Spiritual Psychology and Counseling)
The present study aims to investigate the mediating role of spirituality in the relationship between couples’ marital satisfaction and life satisfaction. The study was conducted following the relational design, one of the quantitative research methods. The study group included 586 married individuals residing in Istanbul, Turkey, of whom 525 were female and 61 were male. Three scales, the Married Life Scale the Life Satisfaction Scale, and the “Spiritual Orientation Scale, were used together with a demographic information form to collect data for the study. Moreover, descriptive statistics, correlation, and regression analyzes were conducted over the course of the study. The analysis findings demonstrated that marital satisfaction predicted life satisfaction and spirituality, that spirituality predicted life satisfaction, and that spirituality played a partial mediating role in the relation between marital satisfaction and life satisfaction. In other words, it was determined that marital satisfaction had both a direct and, via spirituality, a indirect impact on life satisfaction. The findings are discussed in light of the literature.